Financial Incentives and Earnings of Disability Insurance Recipients: Evidence from a Notch Design - Philippe Ruh; Stefan Staubli (Institute of Labor Economics (IZA), 2018)
Most countries reduce Disability Insurance (DI) benefits for beneficiaries earning above a specified threshold. Such an earnings threshold generates a discontinuous increase in tax liability – a notch – and creates an incentive to keep earnings below the threshold. Exploiting such a notch in Austria, we provide transparent and credible identification of the effect of financial incentives on DI beneficiaries' earnings. Using rich administrative data, we document large and sharp bunching at the earnings threshold. However, the elasticity driving these responses is small. Our estimate suggests that relaxing the earnings threshold reduces fiscal cost only if program entry is very inelastic.
Keywords: H53; H55; J14; J21; 330; disability insurance; labor supply; benefit notch; bunching